Common Mutation of Plasminogen Detected in Three Asian Populations by an Amplification Refractory Mutation System and Rapid Automated Capillary Electrophoresis - Ooe, Asako; Kida, Masafumi; Yamazaki, Tomio; Park, Sang-Chul; Hamaguchi, Hideo; Girolami, Antonio; Ichinose, Akitada (Thrombosis and Haemostasis, 1999)
Congenital deficiency and dysfunction of plasminogen (PLG) are associated with a mild thrombotic tendency. To facilitate the genetic diagnosis of dysPLGemia, we combined an amplification refractory mutation system and rapid automated capillary electrophoresis. Two different fluorescence-labeled PLG-specific primers for exon XV were designed so that each DNA amplified by PCR showed fluorescence of a different wavelength. Single peaks were detected for the normal and the mutant Ala601-Thr alleles, respectively. A study of 90 normal Caucasians revealed no individuals with the mutation, whereas its gene frequency was 0.021 in Japanese. This mutation was also detected in Korean and Chinese populations at gene frequencies of 0.016 and 0.015, respectively. All of the Korean and Chinese cases with the mutation had at least one haplotype I of the PLG gene, as did most Japanese cases. The high frequency of the Ala601-Thr mutation among these Asian populations may be due to the founder effect.